Where is the bottleneck? Drones and the paradoxes of digitising medical supplies in Ghana's landscapes of care - Marian Burchardt; René Umlauf (Taylor & Francis Group, 2023)
ABSTRACTImplemented in several African countries, medical drones have emerged as a major infrastructural innovation in national healthcare systems and are widely hailed for improving, if not revolutionising, access to medicine and care for rural populations. Being based on digitally driven, autonomous aviation systems, drones are part of wider efforts to use digital technologies in health systems. In this article, we explore the paradoxes that emerge from definitions of logistics as the bottleneck of quality healthcare. Based on ethnographic research in Ghana, we explore the ways in which drone systems have been built up and justified by private and political actors and used by pharmacists and other healthcare professionals along the supply chain as serving emergencies. However, they have transformed the existing landscape of medical supply chiefly because of the multiple ways in which emergencies are defined. We find that while the introduction of drones has dynamised supply chain processes but also reveals structural bottlenecks, e.g. the lack of medical products and malfunctioning institutions. Situated at the interface of critical studies on infrastructures and medical anthropology, our article contributes to the thriving scholarship on digital innovation in healthcare.